Variables Affecting Tourist Satisfaction at Tapeshwari Buffer Zone Community Homestay in Belaka Municipality - Bastola, Animesh (Journal of Janta Multiple Campus, 2024)
Tourist satisfaction is very important for local community to operate the homestay. This research paper focuses on investigating factors influencing tourist satisfaction in homestays. Its objective is to analyze these variables, understand the types of tourists choosing homestays, and assess the local community's commitment to ensuring tourist satisfaction. This article focuses on Belha village of Belaka Municipality, Udayapur. The research design incorporates both qualitative and quantitative methods, aiming for a comprehensive understanding of the phenomenon through various theories and data collection approaches: preliminary interviews, telephonic interviews, structural interviews, Google surveys etc. have been used. The data collected from 82 participants indicates that Tangibles, Environment, Nutriments and Commitment are the significantly strong predictor of tourist satisfaction and this study further shows that commitment of the homestay operator is much stronger predictor of tourist satisfaction. This study explored the TENC Tangibles, Environment, Nutriments and Commitment) model with 25 measurement items to gauge the satisfaction of tourists staying in the homestay. This shows that Tangibles, Environment, Nutriments and Commitment (TENC) in a homestay lead towards the tourist satisfaction. The homestay should focus on exploring their culture and traditions, updating the tangible facilities and providing trainings to the homestay operators for the better service.